2012
DOI: 10.1002/ejic.201200024
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Gas‐Phase Uranyl Diacetone Alcohol Coordination Complexes by Spectator Ligand Addition

Abstract: Gas-phase addition of a basic ligand to dipositive uranyl coordination complexes comprising diacetone alcohol (DAA) results in water-elimination, which indicates aldol dehydration of DAA to produce mesityl oxide. A novel attribute of the observed gas-phase chemistry is that a ligand exothermically associates to a coordination complex to provide the excitation required to induce chemistry in other ligands, with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Furthermore, it has been demonstrated that the concentration of the ESI solvent in our ion trap is insufficient to form association products. For example, [UO 2 (DAA) 2 ] 2+ (DAA = diacetone alcohol) complexes prepared by ESI from >99% acetone solutions readily add isopropanol injected into the ion trap, with no evidence for addition of the stronger Lewis base acetone . Another example is addition of acetone to [UO 2 (acetone) 4 ] 2+ produced by ESI from acetone solution, which occurs only when acetone gas is directly injected into the ion trap .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been demonstrated that the concentration of the ESI solvent in our ion trap is insufficient to form association products. For example, [UO 2 (DAA) 2 ] 2+ (DAA = diacetone alcohol) complexes prepared by ESI from >99% acetone solutions readily add isopropanol injected into the ion trap, with no evidence for addition of the stronger Lewis base acetone . Another example is addition of acetone to [UO 2 (acetone) 4 ] 2+ produced by ESI from acetone solution, which occurs only when acetone gas is directly injected into the ion trap .…”
Section: Results and Discussionmentioning
confidence: 99%
“…For example, [UO 2 (DAA) 2 ] 2+ (DAA = diacetone alcohol) complexes prepared by ESI from >99% acetone solutions readily add isopropanol injected into the ion trap, with no evidence for addition of the stronger Lewis base acetone. 31 Another example is addition of acetone to [UO 2 (acetone) 4 ] 2+ produced by ESI from acetone solution, which occurs only when acetone gas is directly injected into the ion trap. 32 As shown in Figure S4, Supporting Information, other Ln(L) 2 2+ complexes were produced upon CID (Ln = La, Pr, Gd, Tb).…”
Section: +mentioning
confidence: 99%
“…Natural occurring uranium oxide contains uranium atoms in a variety of oxidation states. UO 2 and UO 3 are known, although many ores with these oxidation states yield U 3 O 8 upon exposure to atmospheric conditions. , When uranium is mined, used in weapons, or stored for long periods, such as in the radioactive sludge found at the Hanford Nuclear Site, environmental contamination can result in the formation of dissolved coordination complexes or small uranium oxide particles. The structure, solvation, and chemistry of these species are therefore of wide interest. Mass spectrometry studies have focused on the reactivity of atomic uranium and its small oxides, including the many coordination complexes formed with small ligand or solvent molecules. The electronic spectroscopy of several small uranium oxide molecules has been reported using photoionization techniques. More recently, results from infrared laser spectroscopy have been described for mass-selected uranium- and uranyl-ion complexes. Theoretical studies on actinide systems have been limited by computational expense in the past, but recent advances in methods and basis sets have facilitated higher quality calculations. Although there has been considerable research on small gas phase ions and their complexes, little is known about larger uranium oxide clusters. , In the present study, we use laser vaporization to produce larger uranium oxide clusters and multiphoton photodissociation to investigate their dissociation products and stabilities.…”
Section: Introductionmentioning
confidence: 99%